2015
DOI: 10.1089/cap.2015.0052
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Psychological Effects of Omega-3/6 Supplements in Male Adolescents with Attention-Deficit/Hyperactivity Disorder: A Randomized, Placebo-Controlled, Clinical Trial

Abstract: Background: An abnormality in long chain-polyunsaturated fatty acid (LC-PUFA) levels has been implicated in attention-deficit/ hyperactivity disorder (ADHD). Studies evaluating LC-PUFA supplementation for therapeutic efficacy in ADHD have shown mixed and, therefore, inconclusive results. Methods: Seventy-six male adolescents (age 12-16 years, mean = 13.7) with ADHD were assessed for the effects of 12 weeks omega-3 and omega-6 supplements on biochemical and psychological outcomes in a randomized, placebo-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 58 publications
0
26
0
3
Order By: Relevance
“…A 12-week RCT comprised of 76 male adolescents with ADHD using a similar dose of fatty acids found that supplementation improved blood levels of EPA, DHA, and total omega-3 fatty acids, though no effects on aggression, impulsivity, or anxiety were seen, possibly due to the smaller study sample size and shorter study length of this trial [ 32 ]. Two other trials have been undertaken using a similar 9 : 3 : 1 ratio of EPA, DHA, and GLA, respectively [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 12-week RCT comprised of 76 male adolescents with ADHD using a similar dose of fatty acids found that supplementation improved blood levels of EPA, DHA, and total omega-3 fatty acids, though no effects on aggression, impulsivity, or anxiety were seen, possibly due to the smaller study sample size and shorter study length of this trial [ 32 ]. Two other trials have been undertaken using a similar 9 : 3 : 1 ratio of EPA, DHA, and GLA, respectively [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies concluded that there were limited associations between omega-3/6 fatty acid supplementation and ADHD outcomes. In one study, Conners' Parent and Teacher Rating Scale was not regarded as being sensitive enough to detect small improvements in the behaviour of male adolescents [ 32 ]. Another work found that a supplement providing 480 mg of linoleic acid and 120 mg of α -linolenic acid ameliorated some ADHD symptoms amongst 7–13-year-olds, although no significant differences were found, possibly because children were unmedicated [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in one study, EPA and DHA supplementation in children with ADHD demonstrated no significant improvements in outcome [89]. Furthermore, no beneficial results were observed in a randomized placebo-controlled clinical trial with EPA and DHA supplementation in children with ADHD [90]. There were increased EPA and DHA concentrations in erythrocyte membranes and improved working memory function on supplementation with a mix of omega-3 FAs [93].…”
Section: Omega-3 Fatty Acids Exert Antioxidant Activitymentioning
confidence: 95%
“…Five RCTs have been conducted to study the effect of complementary treatments in adolescents with ADHD but without SUD: cognitive training [26, 34], neurofeedback [35], dietary supplementation with omega-3/6 fatty acids [36], and physical exercise [37]. None yielded robust evidence that these complementary interventions reduce ADHD symptoms in these patients.…”
Section: Introductionmentioning
confidence: 99%